Is There Any Effect of Reading Habits on Writing Skills for Junior High Students: Apakah Ada Pengaruh Kebiasaan Membaca dengan Keterampilan Menulis untuk Siswa Menengah Pertama - Anisah, Devi Nur; Santoso, Dian Rahma (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to show the influence between reading habits and writing skills among students. This research uses quantitative methods. The population used in this study were seventh grade students of SMP At Tibyan Gempol. The sample used in this study amounted to 70 students. The technique used in data collection is a questionnaire used to measure reading habits and a writing test is used to determine how much students are in writing skills. The results of calculations with SPSS for Windows show that the coefficient of the influence of the variables on reading habits and writing skills is 0.627 and the rtable value at significance = 0.05 with df = 68 is 0.235. So, it can be concluded that the value (0.625) > rtable (0.235). This means that Ha is accepted and Ho is rejected. This means that there is a positive influence between the variable X (Reading Habits) and the variable Y (Writing Skills) in seventh grade students.